Identifying and Overcoming Inefficiencies in Substation Integration Project Execution - Tolvanen, Elias (My University, 2023)
This thesis is written to address causes of inefficiencies and how to overcome such in small substation integration projects. This thesis investigates 29 small projects, which are comparable to small wind farm projects by their size and scope of supply. In addition to these, typical project key figures such as change in sales price, change of gross profit margin are studied against sold and booked hours. The relationships of these figures were also studied. Additionally, a complexity approach has been also considered by assessing a complexity factor rating based on scope of supply, project size and sold hours. The goal of these approaches was to evaluate whether there are relationships or correlation between these figures and use the results on reflecting the results of findings against those. The main theme of this thesis is the evaluation of hours. Additionally, the contribution of different functions for these types of projects is reviewed. This approach enabled the possibility to study the causes of inefficiencies of the projects. This thesis was a mixture of a case study, qualitative research, and quantitative research. This thesis utilized both, quantitative with qualitative methods together, and had a case study type of approach throughout the thesis. This was due to a relatively small sample size combined with the nature of this study. An extensive literature review was conducted to study different perspectives of project management and which type of differences there potentially occurs in the project management literature. It showed that there is a lack of consensus in few topics, which required critical evaluation before drawing any conclusions. However, it showed that while reviewing project management literature, it is important to be aware of the context before. The literature review was a key in preparing managerial implications, which are presented at the end of this thesis. This thesis shows that there are consistent and recurring inefficiencies in studied projects. The results of this thesis also proves that projects which had significant overruns in budgeted hours on average performed poorly. Additionally, those projects where actual hours stayed within sold hours performed generally well, and it was not unusual to these projects to ultimately improve their original gross profit margin. Interestingly, this is a contradicting finding to the results from performed chi-squared test and Fisher’s exact test which proves that there is no relationship between hour overruns and gross profit margin change as such. In conclusion, this thesis did not find a distinct method how to detect possible future inefficiencies during the remainder of the project. This is due to the evident fact that it is impossible to predict the future. However, this thesis found methods and practices which are apt to minimize the risk of such occurring. Whereas it is not possible to detect that an inefficiency is about to occur with certainty, there are factors which by identifying are possible to mitigate.

Tämä diplomityö keskittyy pieniin sähköasemaprojekteihin, tutkien projektitoteutuksen aikana mahdollisesti ilmeneviä epätehokkuuksia, sekä syitä niiden ilmenemiselle että työkaluja niiden ratkaisemiseksi. Työssä tutkitaan 29 toimeksiantajan mittapuulla pientä projektia, jotka ovat kooltaan ja toimituslaajuudeltaan verrattavissa tyypillisiin pieniin tuulivoimaprojekteihin. Lisäksi työssä tarkastellaan tyypillisiä projektin avainlukuja, kuten myyntihinnan ja bruttokateprosentin muutoksia suhteessa myytyihin ja kirjattuihin tunteihin sekä tutkitaan näiden välisiä suhteita. Kompleksisuus on myös otettu huomioon arvioimalla projekteille kompleksisuustekijä, joka perustuu toimituslaajuuteen, projektin kokoon ja myytyihin tunteihin. Näiden lähestymistapojen tavoitteena oli arvioida, onko näiden lukujen välillä yhteyksiä ja peilata löydöksiä niitä vasten. Yksi työn pääteemoista on tuntien tutkiminen monesta eri näkökulmasta. Tämä työ on yhdistelmä osallistuvaa tapaustutkimusta, kvalitatiivista tutkimusta sekä kvan-titatiivista tutkimusta. Tämänkaltainen lähestymistapa valittiin suhteellisen pienestä otoskoosta ja tutkimuksen luonteesta johtuen. Laaja kirjallisuuskatsaus suoritettiin projektinhallinnan eri näkökulmien ja potentiaalisten eroavaisuuksien tarkastelemiseksi. Tulokset osoittivat, että projektinhallintakirjallisuudesta konsensus on vaikea tunnistaa, mikä vaati kriittistä arviointia ennen johtopäätösten arviointia. Kirjallisuuskatsaus oli avainasemassa johtopäätösten ja suositusten valmistelussa, jotka esitellään tämän työn lopussa. Työ osoittaa, että tutkituissa projekteissa on jatkuvia ja toistuvia tehottomuuksia. Se myös todistaa, että ne projektit, joissa budjetoitu tuntimäärä ylittyi merkittävästi, suoriutuivat keskimäärin huonosti. Toisaalta projektit, joissa kirjatut tunnit pysyivät myytyjen tuntien rajoissa, suoriutuivat yleisesti ottaen hyvin, ja ei ollut epätavallista että näiden projektien bruttokateprosentti parani. Tämä on toisaalta pienessä ristiriidassa kahden hypoteesitestin - khiin neliö sekä Fisherin tarkan testin - tulosten kanssa, jotka puolestaan osoittavat, ettei tuntiylijäämien ja bruttokateprosentin muutoksen välillä ole suoraa yhteyttä. Yhteenvetona diplomityössä ei tunnistettu selkeää vedenpitävää menetelmää, joilla olisi mahdollista tunnistaa tulevia tehottomuuksia projektitoteutuksen aikana. Työssä löydettiin kuitenkin menetelmiä ja käytäntöjä, jotka ovat omiaan minimoimaan tällaisten riskien toteutumista. Vaikka tehottomuuden tulevaa ilmenemistä ei voida varmuudella havaita, on olemassa tekijöitä, jotka tunnistamalla voidaan riskiä tehottomuuksien ilmenemisestä lieventää.
Keywords: projects; project management; project planning; project work; fi=Sähkötekniikka|en=Electrical Engineering|; Master´s Programme in Smart Energy